Study on the Optimal Crude Papaya Latex Content of Growing Rabbit Diet under Summer Conditions: Effects on Growth Performance and Immune Status - El-Kholy, K.H.; Zeedan, K.I.; El-Neney; Battaa, A.M.; Zeedan; Omyma, I.; El-Hakim, A.S. Abd (International Journal of Poultry Science, 2008)
The study aimed to evaluate the effect of latex of Carica papaya as feed additive and enzymes complex on performance growing rabbits. A control diet was formulated with an estimated proportion of 18% crude protein and 14% crude fibre. Another three diets were formulated supplementing control diet with 0.1, 0.5 or 0.7% papaya latex. One hundred weaned New Zealand White (NZW) rabbits aged 35 days with an average initial weight of 570 ± 8.30 g (mean ± std. error) were used in the present work (25/diet). Daily weight gain and daily feed intake were recorded from weaning up to 91 d of age (fattening period). At this time seven rabbits from each group were slaughtered and immediately lymphoid organs were taken and weighted. Also, blood samples were collected of seven rabbits from each group. Besides, at the end of the experimental period cell mediated immunity was recorded. In the whole fattening period, final body weight at 91 d and feed efficiency values of growing NZW increased linearly by 296.3 ± 49.5 g (P = 0.001) and 0.052 ± 0.007 g/g (P = 0.001), respectively per each increment of 1 unit of papaya latex inclusion. Daily weight gain during the whole fattening period from 35-91 d increased linearly and quadratically (P < 0.031) as dietary concentrations of papaya latex increased obtaining the highest values by using up to 0.16 papaya latex. Spleen and thymus indexes increased linearly by 0.023 ± 0.006 (P = 0.002) and 0.161 ± 0.025 (P = 0.001), respectively per each increment of 1 unit of papaya latex inclusion. The values of WBCs; lymphocytes and total protein increased linearly by 0.95 ± 0.324 (P = 0.007); 8.83 ± 2.03 (P = 0.002) and 2.11 ± 0.338 (P = 0.001), respectively per each increment of 1 unit of papaya latex inclusion. Cell mediated immunity increased linearly and quadratically (P < 0.002) as papaya latex inclusion, being optimized for 0.54% papaya latex inclusion. In conclusion, the addition of 0.7% latex of Carica papaya to the growing NZW rabbit diets, improved growth and immunity capabilities during summer heat stress.